Variations of Heavy Metals in Green Seaweeds from Karachi Coast of Pakistan (Biological Sciences - PJSIR, 2005)
The main purpose of this study was to quantify heavy metals (Mg, Fe, Mn, Cu, Ni, Zn, Cr, Pb, Co, Cd) in different species of green seaweeds from the coastal areas of Karachi, Pakistan, to determine the seasonal and annual variability in the concentrations of these metals, and to assess the interralationship of their concentration in the green seaweeds. Metal concentrations in the green seaweeds showed significant variations. The accumulation of metals by green seaweed was the highest at Buleji coast, while the species of Caulerpa contained the highest concentrations of different metals as compared with other green seaweeds. Interannual variations were also noted in the accumulation of metal concentrations in the seaweeds. The study shows that the seaweeds, although exposed to metal pollutants, were still within the safe limits and can be commercially utilized